Peningkatan Kompetensi Siswa SMK Siang Surabaya melalui Pelatihan Sensor dan Aktuator - Perwi Darmajanti; Imam Sutrisno; Agus Prawoto; Faris Nofandi (Bulletin of Community Engagement, 2024)
Siang Vocational School in Surabaya is required to equip its students with the latest skills in sensor and actuator technology. One important competency is the ability to use and analyze data from sensors and actuators to diagnose and repair control systems. This training program is designed to develop these skills in class XII students. The objectives of this training include improving students' ability to use sensors and actuators, being able to analyze data from inspections of sensors and actuators, making improvements based on sensor and actuator data. Training methods include providing modules on sensor and actuator technology, discussions, slide presentations on sensor and actuator technology, practical use and analysis of sensors and actuators. The expected results are that students are able to use sensors and actuators skillfully, are able to diagnose damage to sensors and actuators correctly, carry out repairs effectively based on sensor and actuator data. The benefits of this training are increasing the competitiveness of graduates of SMK Siang Surabaya in the world of work, preparing students to face the latest technological developments in the sensor and actuator industry, building students' self-confidence in handling problems on motorbikes. This training program is an important step in preparing students of SMK Siang Surabaya to become a competent sensor and actuator technician and ready to face future industrial challenges.